Numerical Study on the Optical Properties of III-V Quaternary Compounds Aluminium Gallium Indium Phosphide Light Emitting Diode - Aung, Htet Htet; May Su Hlaing; Tin Tin Hla (AI Society & STMIK Indonesia, 2024)
The research works the quaternary compounds of AlGaInP (Aluminium Gallium Indium Phosphide) LEDs that provide luminescence intensity in high-brightness LEDs. AlGaInP LEDs, which are direct bandgap semiconductors with green color emission and a wavelength ranging from 500 to 565 nm, are important in electronics display and liquid crystal backlight applications. Depend on carrier concentration, the desired colors and luminescence intensity, the mole fraction of the quaternary compound is changed and also the bandgap energy. The paper contributions the carrier distribution of holes and electrons, the density of states, and the fermi-dirac distribution function calculated. Based on the carrier concentration, luminescence intensity versus photon energy has been determined. These simulation results are presented using MATLAB simulation with theoretical approach.